Private equity challenge - vetropack´s lbo - Breuer, Marvin (2021)
In this thesis, a Field Lab Work Project with the topic Private Equity Challenge, we assume the role of a private equity fund. Our task is to identify a suitable acquisition target, develop value enhancement measures and finally simulate a complete leveraged buyout. Supporting this process is a financial model. This paper serves as the basis for the presentation of the acquisition target to the Investment Committee, which is responsible for the final investment decision. As a target company we chose Vetropack AG, a manufacturer of glass packaging products for the food and beverage industry.